Toward a contextualized understanding of inside sales: the role of sales development in effective lead funnel management - Terho Harri; Salonen Anna; Yrjänen Meri (Emerald, 2022)
Purpose
The purpose of this study is to provide a contextualized understanding of how business-to-business (B2B) firms use the sales development function for efficient and effective lead funnel management.
Design/methodology/approach
The authors adopted a qualitative field-study approach and interviewed 13 people from eight firms. While software as a service (SaaS) firms are the most prevalent application context for the sales development function, the authors also included respondents from non-SaaS firms to develop an in-depth understanding of the contextualized nature of the sales development process.
Findings
Sales development processes can be applied in outbound prospect-focused, outbound account-based, inbound prospect-focused and inbound account-based lead management contexts. The sales development processes of lead research, engagement and handover vary depending on the nature of the lead management context. These processes are supported by the appropriate design of organizational, technological and people platforms.
Practical implications
The authors explain how sales development as a form of inside sales can support effective lead funnel management in B2B firms through technology-enabled lead research and nurture processes designed to prepare customers for meaningful conversations with field sales.
Originality/value
To the best of the authors' knowledge, this study is the first to focus purely on the sales development function as a form of inside sales. They explain how the sales development processes relating to lead research, engagement and handover are conducted in four distinct application contexts to qualify leads for the outside salesforce.